The effects of social exclusion on response inhibition in borderline personality disorder and major depression. (April 2018) - Ernst, Mareike; Mohr, Harald M.; Schött, Margerete; Rickmeyer, Constanze; Fischmann, Tamara; Leuzinger-Bohleber, Marianne; Weiß, Heinz; Grabhorn, Ralph
Abstract: It is a prevalent notion that borderline personality disorder (BPD) is characterized by deficits in executive functions (EF) like inhibition. Yet experimental studies yield inconsistent results. However, despite emotional dysregulation being a core feature of BPD, most paradigms did not control for emotional state or comorbid mental disorders. In the present study, subjects with BPD and comorbid MDD (BPD+MDD), with major depression (MDD) and healthy controls (HC) partook in a social exclusion paradigm combined with an inhibition task. We expected inhibition to be more strongly impaired in BPD+MDD than in depression and HC when experiencing negative emotions. Respecting inhibition, depressed patients performed best while (BPD+MDD) patients performed worst. Surprisingly, MDD & HC participants' performance improved during social exclusion, but this was not the case for BPD+MDD. Inhibition deficits were correlated with childhood trauma. These results challenge the hypothesis that an induction of negative emotion results in inferior inhibition in (BPD+MDD). Instead, patients with (BPD+MDD) seem to suffer from a more general inhibitory dysfunction. Importantly, (BPD+MDD) patients were not able to improve their performance during social exclusion like HC and MDD patients did. These findings need to be investigated further, particularly regarding the efficiency of neural networks regulating inhibition and effects of trauma. Highlights: Inhibition-deficits in BDP with depression could not be attributed to the extent of emotion dysregulation/heightened arousal. Depressed patients showed improved inhibition performance during the experience of social exclusion. The more general inhibitory deficits observed in BPD patients might be related to childhood trauma.